Psychological Inflexibility and Anxiety: The Role of Self-Compassion as a Mediator - Sita, Laras; Bintari, Dini Rahma (Analitika: Jurnal Magister Psikologi UMA, 2025)
Anxiety is one of the most common mental health issues experienced by individuals in early adulthood. One contributing factor to anxiety is psychological inflexibility, characterized by rigid and maladaptive responses to internal experiences. Conversely, self-compassion is known to serve a protective role by promoting emotional resilience and reducing anxiety. This study aimed to examine the effect of psychological inflexibility on anxiety with self-compassion as a mediating variable. A quantitative descriptive approach was employed, and data were collected through questionnaires distributed to 183 early adults. The instruments used were the Acceptance and Action Questionnaire-II (AAQ-II) to measure psychological inflexibility, the Self-Compassion Scale (SCS) to assess self-compassion, and the State-Trait Anxiety Inventory (STAI) to measure anxiety levels. The results revealed that self-compassion significantly mediated the relationship between psychological inflexibility and anxiety. These findings highlight the crucial role of enhancing self-compassion in mitigating the negative impact of psychological inflexibility on anxiety among early adults.